The Quantum Nature of Drug-Receptor Interactions: Deuteration Changes Binding Affinities for Histamine Receptor Ligands - Kržan, Mojca (PLoS One, 2016)
In this article we report a combined experimental and computational study concerning the effects of deuteration on the binding of histamine and two other histaminergic agonists to (3)H-tiotidine-labeled histamine H2 receptor in neonatal rat astrocytes. Binding affinities were measured by displacing radiolabeled tiotidine from H2 receptor binding sites present on cultured neonatal rat astrocytes. Quantum-chemical calculations were performed by employing the empirical quantization of nuclear motion within a cluster model of the receptor binding site extracted from the homology model of the entire H2 receptor. Structure of H2 receptor built by homology modelling is attached in the supporting information (S1 Table) Experiments clearly demonstrate that deuteration affects the binding by increasing the affinity for histamine and reducing it for 2-methylhistamine, while basically leaving it unchanged for 4-methylhistamine. Ab initio quantum-chemical calculations on the cluster system extracted from the homology H2 model along with the implicit quantization of the acidic N–H and O–H bonds demonstrate that these changes in the binding can be rationalized by the altered strength of the hydrogen bonding upon deuteration known as the Ubbelohde effect. Our computational analysis also reveals a new mechanism of histamine binding, which underlines an important role of Tyr250 residue. The present work is, to our best knowledge, the first study of nuclear quantum effects on ligand receptor binding. The ligand H/D substitution is relevant for therapy in the context of perdeuterated and thus more stable drugs that are expected to enter therapeutic practice in the near future. Moreover, presented approach may contribute towards understanding receptor activation, while a distant goal remains in silico discrimination between agonists and antagonists based on the receptor structure.